Continuous improvement and organizational practices in service firms: exploring impact on cost reduction - Koval, Oksana; Nabareseh, Stephen; Stankalla, Roland; Chromjakova, Felicita (Serbian Journal of Management, 2019)
A growing importance of services sectors for global trade invokes the question of how to combat the innate complexity and inefficiency of service operations. As a response to the growing request for enhancement of service efficiency, companies implement Continuous Improvement (CI) initiatives to reduce costs of operations. However, the researchers failed to reach consensus on the effect of CI operations efficiency in non-manufacturing environment. Thus, the proposed study attempts to answer an important question of impact of CI on cost reduction in the services environment by applying Structural Equation Modeling to the 304 survey responses collected in the course of the study. Furthermore, the research investigates how organizational practices impact relationship between CI and cost reduction. The study suggests that CI itself is unable to reduce costs and requires a support of multiple organizational practices, such as Rewards and Recognition of Employees, Quality Culture, Employee Training and Goal setting, to obtain the benefits of cost reduction. Consequently, the research results allow for a conclusion with a vast practical implication that there is need to develop a comprehensive infrastructure of organizational practices to support CI in order to attain cost reduction. The research findings provide recommendations for CI implementation and investment prioritization in service organizations.